Begonia datii (sect. Coelocentrum Begoniaceae), a new species from Quang Binh Province, Central Vietnam - Hoang, Thanh Son; Lin, Che-Wei (Phytotaxa, 2023)
Begonia datii, a new species of B. sect. Coelocentrum from Central Vietnam is described. It resembles B. filiformis in its habit, leaf shape and texture, but it can be easily distinguished from the latter by its peduncle and inflorescence covered with villous hairs (vs. glandular-hispid), bracts caducous (vs. persistent or semi-persistent), tepals pinkish-white to pink (vs. yellowish-green), glabrous outer tepals of pistillate flowers (vs. glandular-hispid abaxially), ovary and wings glabrous (vs. glandular-hispid). Also, the two species can be clearly separated by geographical distributions: Begonia datii occurs only in Quang Binh Province, where is separated from the nearest known population of B. filiformis by ca. 450 km in southwestern Guangxi of China.